2019
DOI: 10.3390/ijerph16193691
|View full text |Cite
|
Sign up to set email alerts
|

Our Healthy Clarence: A Community-Driven Wellbeing Initiative

Abstract: In 2015–2016, the Clarence Valley in Northern New South Wales, Australia, experienced an unexpectedly high number of deaths by suicide, and the resulting distress was exacerbated by unhelpful press coverage. The local response was to adopt a community-wide positive mental health and wellbeing initiative. This paper describes the process and achievements of the initiative called ‘Our Healthy Clarence’. Key stakeholders were interviewed at year two and relevant documents reviewed. Data were analysed using docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…There are similarities between our study findings and the themes identified in other community-driven, mental wellbeing initiatives, e.g., ‘Our Healthy Clarence’ program [ 8 ]. Similarities were noted with the use of a strengths-based approach with a focus on mental wellbeing, increasing hope, communication, inclusivity, and collaboration [ 8 ]. However, WoW does not rely on governance and formal structures to succeed but instead relies on community members to take ownership and champion success.…”
Section: Discussionsupporting
confidence: 77%
“…There are similarities between our study findings and the themes identified in other community-driven, mental wellbeing initiatives, e.g., ‘Our Healthy Clarence’ program [ 8 ]. Similarities were noted with the use of a strengths-based approach with a focus on mental wellbeing, increasing hope, communication, inclusivity, and collaboration [ 8 ]. However, WoW does not rely on governance and formal structures to succeed but instead relies on community members to take ownership and champion success.…”
Section: Discussionsupporting
confidence: 77%
“…By making small changes in my activities, I can meet my goal to be happier and healthier. The application of strengths-based approaches has increasingly been used in diverse environments (such as the workplace and clinical settings [45,50,52,54,55]), communities, and populations (e.g., children, Indigenous communities) [48,49,[56][57][58][59]. For instance, Zhang et al [50] in a recent systematic review and meta-analysis of randomized controlled trials, revealed that strengths-based, solution-focused brief therapy in medical settings had a significant effect on health-related psychosocial outcomes (e.g., depression, psychosocial adjustment to illness), with positive indicators for health-related behavioral outcomes (e.g., physical activity, nutrition score).…”
Section: Person-centered Messagingmentioning
confidence: 99%
“…Seven articles featured initiatives targeted at Aboriginal and Torres Strait Islander Peoples (henceforth, respectfully, Aboriginal Peoples), [26][27][28][29][30][31][32] two of those targeted young people (one for secondary school students and one for 16-26 years), 31,32 and one involved older people. 26 Seven others targeted general rural populations: five for people of all ages 18,24,25,33,34 ; one targeted 12-18 year-olds 35 ; and one targeted people with dementia and their carers. 36 Some initiatives were centred on specific places, including an arts and craft centre, art exhibition spaces, secondary schools, a cultural camp and gardens.…”
Section: Populations and Settingsmentioning
confidence: 99%
“…Other issues include reticence to seek out services due to fear of stigma 1 and confusion about navigating services arising from a mental health system described as highly fragmented. 17 To address poor local well-being and self-harm, some communities have taken matters into their own hands, 18,19 with anecdotal evidence of community co-produced mental health, well-being and suicide prevention programs emerging. [4][5][6] A recent report categorised these as 'community well-being' (targeted at awareness-raising) and 'early intervention' (early conversations and referrals) initiatives where rural communities had mobilised to address local mental health challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation